Social Capital and Health Outcomes of Elderly People - Seo Bosu (Journal of Aging Research And Healthcare, 2018)
Greater social capital has been shown to be associated with improved mental health, general wellbeing and reduced risk of premature mortality, cancer mortality and cardiovascular mortality. However, most of these studies found a positive relationship between social capital and health are limited to descriptive studies. This project is performing a theoretical approach to the role of social capital in producing health outcome based on Becker’s household production function. We are testing whether social capital has a positive impact on health both directly through a more effective production of health and indirectly through utilizing the health care system better, using several measurements of social capital from ‘social support’ module in the National Health and Nutrition Examination Survey (NHANES) 2007-2008 for a sample of those 60 years old and above. NHANES is a unique data set in terms of collecting both subjective self-rated health status and several objective health outcome measurement through medical and laboratory examination. Finding from 2SLS with instrumental variable was a bit surprising – various social capital measures do not show significant results in different experiments. The only exception is that more resources of emotional support can promote better overall health status.
Keywords: social capital